PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MODERASI - Yudhistira Adwimurti; Sumarhadi Sumarhadi (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The problem in this study is the effect of price, promotion and product quality on purchasing decisions at the Bogor Belibis Curly Noodle Culinary Business. The purpose of this study was to determine the effect of price, promotion and product quality on purchasing decisions of Belibis Curly Noodles. The sampling technique used accidental sampling so that a sample of 100 respondents was obtained. Methods of data collection using observation and questionnaires. The data that has been collected is then processed with data processing techniques used to test the validity and reliability. Data analysis techniques include t-test, coefficient of determination test, multiple linear regression test and f-test. From the results of the research hypothesis test, it was found that H1, H2, H3, H4 and H5 were accepted or in other words the price, promotion, and product quality variables had a positive and significant effect on purchasing decisions. In addition, the hypothesis test regarding moderation also shows that product quality strengthens the effect of price and promotion on purchasing decisions.